A roadmap for tailoring the strength and ductility of ferritic/martensitic T91 steel via thermo-mechanical treatment. (15th June 2016) - Song, M.; Sun, C.; Fan, Z.; Chen, Y.; Zhu, R.; Yu, K.Y.; Hartwig, K.T.; Wang, H.; Zhang, X.
Abstract: Ferritic/martensitic (F/M) steels with high strength and excellent ductility are important candidate materials for the life extension of the current nuclear reactors and the design of next generation nuclear reactors. Recent studies show that equal channel angular extrusion (ECAE) was able to improve mechanical strength of ferritic T91 steels moderately. Here, we examine several strategies to further enhance the mechanical strength of T91 while maintaining its ductility. Certain thermo-mechanical treatment (TMT) processes enabled by combinations of ECAE, water quench, and tempering may lead to "ductile martensite" with exceptionally high strength in T91 steel. The evolution of microstructures and mechanical properties of T91 steel were investigated in detail, and transition carbides were identified in water quenched T91 steel. This study provides guidelines for tailoring the microstructure and mechanical properties of T91 steel via ECAE enabled TMT for an improved combination of strength and ductility. Graphical abstract: